A new species of Pollenia Robineau-Desvoidy, 1830 from Jordan (Diptera: Calliphoridae: Polleniinae) - Rognes, Knut (Zootaxa, 2016)
A new species, Pollenia bartaki sp. nov., assigned to the Pollenia rudis species-group in Pollenia Robineau-Desvoidy, 1830, is described on the basis of a single male specimen captured in Jordan. Its strongly curved surstylus is unique in the genus. The nominal species Pollenia aurata Séguy, 1934 and P. bazini Séguy, 1934 are formally transferred to the genus Xanthotryxus Aldrich, 1930, comb. nov.